The Effect of Stocking Density on the Growth and Survival Rate of Catfish(Hemibagrusnemurus)WithBiofloc Technology on Peat Swamp Water - Fitri Ismael; Usman M. Tang; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted on May 13 to June 22 on 2018 at Aquaculture TechnologyLaboratory, Department of Aquaculture, Faculty of Fisheries and Marine University of Riau. The aim of study is to know the best stocking density on growth and survival rate of catfish(Hemibagrusnemurus) with bioflok technology on peat swamp waters. The method used is Completely Randomized Design (CDR) with 1 (one) factor consisting of 4 (four) treatment levels and three repicates. The standard of trement used is stocking density 12 individuals/40L, 16 individuals/40L, 20 individuals/40L and 24 individuals/40L. During 40 days maintenace of of the best treatment on stocking density 24 individuals/40L with an absolute weigh of 4,34 gram, absolute length 5,51 cm, daitly growth rate 6,30%/days, efficient feed 93,14%, feed conversion ratio 1,07 and 97,22% of survival rate.And the quality of water during the study is the temperature of 25-17 0 C, pH 4-7, dissolved oxygen 4.0-5.2 and ammonia 0.3047-0.4484. Key Word : Hemibagrusnemurus, Stocking Density, Bioflok, Peat Swamp Water.